2020
DOI: 10.5694/mja2.50522
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant‐induced sexual dysfunction

Abstract: S exual dysfunction can be subdivided into disorders of sexual drive (usually loss of libido), disorders of arousal and disorders of orgasm and ejaculation, as well as other problems including dyspareunia and priapism. 1 An extensive literature search was undertaken to explore the evidence about antidepressant-induced sexual dysfunction. This included an online search of the MEDLINE, EMBASE, PubMed and Cochrane databases, along with relevant websites and texts and reference lists from identified articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 62 publications
3
82
1
2
Order By: Relevance
“…However, the exact biological, psychological, and social mechanisms underlying the pathogenesis of depression remain largely unknown. Currently, most patients with depression are treated with synthetic drugs including selective serotonin reuptake inhibitors (SSRI) that act on the monoaminergic system, serotonin-norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants (TCAs), norepinephrine and dopamine reuptake blockers, and monoamine oxidase inhibitors which exhibit little or no improvement on depression and have side effects such as fatigue, sleep disorders, cognitive disorders, and sexual dysfunctions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact biological, psychological, and social mechanisms underlying the pathogenesis of depression remain largely unknown. Currently, most patients with depression are treated with synthetic drugs including selective serotonin reuptake inhibitors (SSRI) that act on the monoaminergic system, serotonin-norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants (TCAs), norepinephrine and dopamine reuptake blockers, and monoamine oxidase inhibitors which exhibit little or no improvement on depression and have side effects such as fatigue, sleep disorders, cognitive disorders, and sexual dysfunctions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Indeed, an emerging body of research suggests considering treatment discontinuation for some long-term users. [11][12][13][14] Prolonged use is a concern because of the potential for avoidable side effects and serious adverse events, including upper gastro-intestinal bleeding, hyponatremia, stroke, falls and fractures, [15][16][17] alongside emotional numbing, weight gain, sleep disturbance, sexual dysfunction, 18,19 and loss of personal agency. 20 General practice is the setting in which depression is most commonly treated and antidepressants initiated and maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we recently found that LPS could cause the depressive-like behaviors in mice via activating RagA/mTOR/p70S6K pathway [ 8 ]. As for the therapy of depression, the conventional antidepressant drugs are challenged by gastrointestinal and sexual side effects [ 38 , 39 ]. Interestingly, we recently discovered that botanical drug puerarin could effectively attenuate depression and pain in mice with SNI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%